2017
DOI: 10.1016/j.devcel.2016.12.014
|View full text |Cite
|
Sign up to set email alerts
|

CENP-A Modifications on Ser68 and Lys124 Are Dispensable for Establishment, Maintenance, and Long-Term Function of Human Centromeres

Abstract: CENP-A is a histone H3 variant key to epigenetic specification of mammalian centromeres. Using transient overexpression of CENP-A mutants, two recent reports in Developmental Cell proposed essential centromere functions for post-translational modifications of human CENP-A. Phosphorylation at Ser68 was proposed to have an essential role in CENP-A deposition at centromeres. Blockage of ubiquitination at Lys124 was proposed to abrogate localization of CENP-A to the centromere. Following gene inactivation and repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 40 publications
5
66
5
Order By: Relevance
“…CDK1/2 and PLK1 impact the timing of new CENP-A deposition by phosphorylating M18BP1 and HJURP in HeLa and other cell lines (18,19,49). Another study in HeLa suggested that phosphorylation of CENP-A at Ser68 by Cyclin B1/CDK1 prevents premature CENP-A loading (20), despite some debates (21,22). While these studies highlighted important “normal” regulation that ensures proper centromere assembly, their roles in any clearly defined cancer model or in normal primary cells are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…CDK1/2 and PLK1 impact the timing of new CENP-A deposition by phosphorylating M18BP1 and HJURP in HeLa and other cell lines (18,19,49). Another study in HeLa suggested that phosphorylation of CENP-A at Ser68 by Cyclin B1/CDK1 prevents premature CENP-A loading (20), despite some debates (21,22). While these studies highlighted important “normal” regulation that ensures proper centromere assembly, their roles in any clearly defined cancer model or in normal primary cells are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…While Lys124 does not lie within the CATD, which is sufficient for CENP-A deposition [42], the size of the ubiquitin moiety could bridge the distance and contribute to HJURP binding. Despite the intriguing biochemical data, gene replacement experiments show that mutant CENP-A that cannot be ubiquitylated, can completely replace the endogenous CENP-A and support cell viability [43]. Therefore, direct ubiquitylation of CENP-A by CUL4 does not play an essential role in CENP-A deposition; although, we cannot preclude that Lys124 modification may play important roles under certain cellular conditions.…”
Section: Pre-nucleosomal Posttranslational Modification Of Centromerimentioning
confidence: 95%
“…There are conflicting data about the importance of Ser68 phosphorylation in cells. Fachinetti et al [43] show no effect of a phosphomimetic mutant of Ser68 (S68D) on cell viability in gene replacement assays; whereas, Wang et al [61] show that cell viability is reduced to 50% when the non-phosphorylated mutant (S68A) is introduced into the endogenous CENP-A locus by CRISPR. Ser18 within the amino terminal tail of CENP-A has also been proposed to negatively regulate CENP-A deposition; however, the mechanism is unknown [11].…”
Section: Cell Cycle Control Of Centromere Inheritancementioning
confidence: 99%
“…In order to address this question, Fachinetti and colleagues attempted to rescue CENP-A knockout RPE (retinal pigment epithelium) cells by expressing CENP-A modification mutants by viral transduction. In these experiments, individual Ser-68 phosphomimetic mutants, or unmodifiable Lys-124 mutant, rescued cell viability resulting from loss of endogenous CENP-A (Fachinetti et al 2017). Potential caveats of these experiments, including the degree to which mutant CENP-A overexpression may compensate for loss of CENP-A modifications have been proposed to support the importance of the Lys–124 and Ser-68 modifications at the cellular level (Niikura et al 2017a; Wang et al 2017).…”
Section: Cenp-a Posttranslational Modifications and Deposition At Cenmentioning
confidence: 97%
“…Indeed, Fachinetti and colleagues observed that LacI-fused CENP-A–S68Q mutant reduced HJURP recruitment at LacO array, which is in agreement with a negative role for Ser-68 phosphorylation in HJURP binding as reported by Guohong and colleagues. In contrast, these same experiments showed that the CENP-A–K124R mutant was as efficient as wild-type CENP-A in recruiting HJRUP to the LacO site (Fachinetti et al 2017), casting additional doubt on whether K124 affects CENP-A deposition through the proposed model. The contradiction between the apparent biochemical impact of these mutations and the fact that they are dispensable for cell viability may suggest that while Ser-68 and Lys-124 are not absolutely required to regulate CENP-A recognition by HJURP, these modifications are likely to play a subtle modulatory role in CENP-A deposition than originally described.…”
Section: Cenp-a Posttranslational Modifications and Deposition At Cenmentioning
confidence: 98%